SHAHU MAHARAJA’S VISION OF A CASTELESS SOCIETY: IDEALS, CHALLENGES, AND LEGACY (International Journal of Food and Nutritional Sciences, 2020)
This research paper examines Shahu Maharaja’s vision of a casteless society, delving into his ideological framework, the obstacles he encountered, and his enduring legacy on Indian social structures. Shahu Maharaja dedicated significant resources to the cause of social reconstruction, striving to modernize a caste-ridden society into one aligned with democratic and scientific principles. His initiatives included integrating non-Brahmins into government services, founding educational institutions for the untouchables, and championing social reform through various movements. The Maharaja's efforts to combat caste discrimination and promote social equality were met with resistance from entrenched caste hierarchies, yet his progressive policies laid the groundwork for substantial social change. This paper explores Shahu Maharaja’s strategic approaches, such as advocating for "self-help," opposing untouchability, and endorsing intercaste marriages, and assesses the impact of his reforms on the social fabric of his time. Ultimately, it highlights how his pioneering work continues to resonate in contemporary discussions on social equity and reform.